Syphilis as osteomyelitis of the fifth metatarsal of the left foot: the great imitator hits once again. (July 2020) - Gaspari, Valeria; Mazza, Liliana; Pinto, Daniela; Raone, Beatrice; Calogero, Pietro; Patrizi, Annalisa
Abstract: Introduction: We report an unusual case of osteomyelitis of the left foot due to syphilitic bone involvement. Case presentation: A 73-year-old man came to our attention with a four-month history of fever and a hypertrophic ulceration of the fifth metatarsal of the left foot. He had a history of syphilis treated years before. The CT scan showed an evident osteolytic area of the metatarsal phalangeal joint of the fifth left toe. The serological tests demonstrated a syphilitic reinfection. On suspicion of a bone localization of syphilis, an US-guided bone biopsy was performed. The histological examination with silver impregnation confirmed the diagnosis. The patient was treated with the traditional treatment of syphilis using penicillin, obtaining the complete resolution of the radiological and cutaneous alterations. Conclusions: The aim of this work is to sensitize clinicians to suspect syphilis in case of osteolytic lesions in patients with a history of this disease.